O processo sucessório em empresas familiares paulistas: uma abordagem psicológica sobre a família empresária - Paranhos, Marina (2015)
The present work had as its aims: 1) to understand how time perception influences the succession process in family business; 2) to comprehend how the family myths affect the succession process in family business; 3) to perceive how occurs the links in dimensional spaces along with the succession process in family business. We adopted a qualitative investigation approach through case study. The analysis is taken under the systemic perspective. Had participated of this research: three family member of business family in its first generation; three family member of business family in its second generation; three family member of business family in its third generation with ages between 29 and 58 years old, from both genders. We used the following methods: semi-structure interviews, genogram and observation. The results show that the life cycle of both - family and business, influences the way of thinking and planning succession. We also identified the impact of the family myths on the succession process by repetition of the preceded generation models or by adjusting and transforming the myths according to the family, business and individual demands. The results also indicate different types of space appropriation: through resistance to actions or by innovations movements that embrace the symbolic identification with the family business place. Suggestions for future research are presented and the relevance of including the dimensional space in the family business area of studies are stressed